Science Teaching Practices at Secondary Level: Cross Comparison of Public and Private Sector Teachers (Journal of Asian Development Studies, 2024)
The main purpose of the study was to learn about science education practices in both public and private schools and identify effective teaching practices in both sectors. To fulfil this purpose, a comparison between public teachers with private teachers and public students with private students was made. For this purpose, a random sample of 300 secondary school students and 80 teachers were selected to collect data. The selected teachers and students were given two rating scales as instruments to learn howto utilize teaching practices. The data were analyzed through the Statistical Package for Social Sciences (SPSS). To examine the gathered information, descriptive data analysis statistics and inferential statistics were used to diagnose the practices. Data analysis highlighted that male secondary school teachers in public and private schools needed to be successfully teaching science. The results led to the recommendation that all the teachers, particularly those employed by private institutions, should undergo refresher courses for effective science teaching practices training